Kemajuan Seni Suara Dalam Tradisi Bani Umayyah - Ahmad Mustaqim (MIQOT, 2021)
This study is entitled about the Progress of Sound Art in the Bani Umayyah Tradition, the focus of this research is the beginning of the tradition of sound art in theBani Umayyah , the initiator of the art of music and the existence of the genre of sound art and the culmination of the progress of sound art. This research is a historical research using a historical approach and data corruption data that leads to the interpretation of the interpretation of the facts as a whole. And the method used in this research is the Library Reserch method which takes data from books, journals, and other scientific works. The results obtained from this study can be concluded several kinds, namely, the art of sound or music has existed since the time of Rasullullah, and the very dominant figure in developing the art of sound is Ziryab, then the peak of the existence of the art of music during the Dynasty Umayyah was in Andalusia, precisely Umayyah II.Â Kata Kunci : Dynasty Umayyah , Sound Art, Music Art, Ziryab.